GHS-R1a constitutive activity and its physiological relevance - MEAR, Yves L.; ENJALBERT, Alain; THIRION, Sylvie (Frontiers in Neuroscience, 2013)
Abundant evidences have shown that ghrelin, by its binding to GHS-R1a, plays an important role for fundamental physiological functions. Increasing attention is given to the GHS-R1a unusually high constitutive activity and its contribution to downstream signalling and physiological processes. Here, we review recent lines of evidences showing that the interaction between ligand-binding pocket TM domains and the ECL2 could be partially responsible for this high constitutive activity. Interestingly, GHSR-1a constitutive activity activates in turn the downstream PLC, PKC and CRE signalling pathways and this activation is reversed by the inverse agonist [D-Arg1, D-Phe5, D-Trp7,9, Leu11]-substance P (MSP). Noteworthy, GHSR-1a exhibits a C-terminal-dependent constitutive internalization. Non-sense GHS-R1a mutation (Ala204Glu), first discovered in Moroccan patients, supports the role of GHSR-1a constitutive activity in physiological impairments. Ala204Glu-point mutation, altering exclusively the GHSR-1a constitutive activity, was associated with familial short stature syndrome. Altogether, these findings suggest that GHS-R1a constitutive activity could contribute to GH secretion or body weight regulation. Consequently, future research on basic and clinical applications of GHS-R1a inverse agonists will be challenging and potentially rewarding.